Hubungan Loneliness dengan Fear of Missing Out (FoMO) pada Ibu Bekerja yang Mengalami LDM di Sumatera Barat - Muzhdhalifatul Azizah; Yolivia Irna Aviani (Pusat riset dan Inovasi Nasional, 2025)
This study aims to examine the correlation between loneliness and Fear of Missing Out (FoMO) among working mothers experiencing long-distance marriage (LDM) in West Sumatra, a population facing dual challenges of work responsibilities and limited spousal support. Loneliness, often triggered by the lack of emotional closeness and reduced social support, is hypothesized to significantly contribute to FoMO, particularly in the context of increased social media use. The research employed a quantitative correlational design with a sample of 385 working mothers selected through simple random sampling. Data collection utilized the FoMO scale developed by Kurniawan and Utami (2022) and a loneliness scale designed by the researcher based on Russell’s (1996) dimensions. Data analysis used the Pearson product moment correlation test after ensuring normality and linearity assumptions were met. The findings revealed a significant positive correlation between loneliness and FoMO (r = 0.649, p < 0.05). This indicates that higher levels of loneliness are associated with greater FoMO tendencies among working mothers living apart from their spouses. The study highlights how psychological vulnerabilities related to marital separation and dual roles increase susceptibility to FoMO. These results underscore the importance of providing psychosocial support, strengthening marital communication, and promoting digital literacy to reduce FoMO risks. This research contributes to understanding the psychosocial dynamics of working mothers in LDM contexts and can serve as a basis for preventive interventions to enhance mental well-being.